Pembangunan Sistem Informasi Anak Pada Posyandu Cilongkeang Desa Dirgahayu Berbasis Web - Dewi Rosmala; Muhammad Hafizh Al Faritsi; Sarah Nurul Izzati; Faisal Fadilah; Anisha Maladari (Lembaga Pengembangan Kinerja Dosen, 2024)
The development of a web-based Child Information System at Posyandu Cilongkeang, Dirgahayu Village, aims to address the challenges of manual record-keeping, which is time-consuming, prone to loss, and causes data errors. This system is designed to support child health recording activities, providing fast and accurate nutritional status information of toddlers. The research method involved observation, interviews, and system testing, including User Acceptance Testing (UAT). The result shows that this web-based information system improves operational efficiency and data accuracy at the posyandu, while also providing IT training to posyandu cadres. The system has proven effective in reducing recording errors and speeding up the reporting process